(untitled) (Quinto Sol, 2021)
This article analyzes the Malvinas war from a global perspective, understanding the direction that it took on as intertwined with the international context of the Cold War. To this end, the emphasis is placed on the analysis of the United States policy, first a diplomatic one and then an interventionist one, as an ally of Great Britain. Analyzing the bilateral conversations between Margaret Thatcher and Ronald Reagan together with official statements and publications of different US state agencies, it can be seen the way in which the development of the Malvinas war, beyond the regional particularities that triggered it, was inserted within the anti-Soviet logic of the second Cold War. Added to this is a global context of the imposition of neoliberal policies that radicalized the US intervention in Latin America in favor of the imposition of its capitalist imperialist model.